Forensic science capacity development: A case study of Timor-Leste - Loene M. Howes; Roberta Julian; Renee Wilson; Maria C. dos Santos (Forensic Science International: Synergy)
Forensic science is socially constructed within particular contexts, with notable challenges for countries of the Global South. This study explored forensic capacity development taking place under a bilateral agreement between the governments of Timor-Leste and Australia through the Timor-Leste Police Development Program. Data were collected through in-country site visits, observations, and interviews with key personnel from both countries. The findings indicate tangible developments, including the establishment of a forensic fingerprint laboratory, training in fingerprint expertise from crime scene to court, and engagement in innovative practices. These developments contribute to optimism amongst leaders and practitioners about the potential for forensic capacity. However, concerns exist about the precariousness of achievements, the need for continued training and development within and beyond the forensic team, untapped potential for inter-agency collaboration, and other human resource considerations. The findings suggest a need for organisational commitment and ongoing high-quality partnerships to maintain momentum and facilitate long-term sustainability.